Pelatihan dan Pendampingan Penggunaan Liveworksheets dalam Pembuatan Lembar Kerja Peserta Didik bagi MGMP Madrasah Tsanawiyah Matematika Rayon 2 Se-Kota Jambi - Risnita Risnita; Fitri Kumala Dewi; Defina Dwi Bulan; Marni Zulyanty; Ainun Mardia (Universitas Muhammadiyah Semarang, 2023)
The purpose of this Community Service (PkM) activity is to maximize the use of the Liveworkssheets platform. In carrying out service, the method used is Asset Based Community-driven Development. The training and mentoring process begins with the first stage being pre-implementation, the second stage is the implementation of research, and the third stage is research evaluation which is divided into five stages (Define, Discovery, Dream, Design, and Deliver or Destiny). This activity was attended by 15 mathematics teachers who are members of the MGMP Mathematics MTs/SMP Rayon 2 Jambi City community. The results of the activities include: 1) Increased understanding from MGMP Mathematics MTs/SMP Rayon 2 Jambi City teachers about the importance of digital literacy. 2)Increased technical knowledge of participants from initially not knowing to knowing after getting training using the Liveworksheets platform. 3)Teachers are interested in using the liveworksheets platform when compiling questions for the purposes of midterm tests or end-of-semester tests because of the ease of compiling and checking students' answers.